Energy Optimized Routing Algorithm for Hybrid Wireless Mesh Networks in Coal Mine. (19th October 2015) - Jiang, Haifeng; Sun, Renke; Ma, Shanshan
Abstract : Mesh clients in hybrid wireless mesh networks can participate in networking and routing. When the backbone transmission network is broken, the mesh client can route and forward the data, which will eliminate the absolute dependence on the backbone network of traditional infrastructure wireless mesh networks in mine emergency rescue. However, the energy of mesh clients is limited. Based on the comprehensive consideration of the efficiency and balance of energy consumption of mesh clients for data transmission, a new energy cost criterion is designed. Energy optimized and fault recovered routing algorithm is proposed on account of different network states. At last, the simulation analysis on the performance of routing algorithm is conducted and compared with typical routing algorithms. Simulation results show that the algorithm has effectively extended the network lifetime and achieved optimized combination of energy efficiency and energy balance. When mesh routers in the backbone network are failed, this algorithm can rapidly rebuild the route and shows strong capacity of routing recovery.